Ultrasonographic evaluation of joint capsule swelling of shoulders and hips in hemodialysis patients - Aoyagi, Ryuzi (Journal of Japanese Society for Dialysis Therapy, 1992)
In order to clarify the pathogenesis of dialysis arthropathy, ultrasonographic evaluation of the soft tissues of the shoulder and hip joints was performed. SCD (shoulder-capsular distance) and HCD (hip-capsular distance) were measured as a marker of joint capsule swelling. The ralationship between these parameters and clinical or laboratory findings was examined. We studied 168 HD patients (116 males, 52 females), of whom the mean age was 49.4±12.2 years and the mean HD duration 107.0±75.6 months. Ten healthy subjects with normal renal function were evaluated as a control group. Mean-SCD and mean-HCD were significantly wider in HD patients than in control subjects (mean-SCD: 6.8±1.7mm vs 5.5±0.9mm, p<0.05, mean-HCD: 17.5±5.5mm vs 13.6±1.5mm, p<0.01). These parameters correlated with the HD duration (mean-SCD: r=0.696, p<0.001, mean-HCD: r=0.606, p<0.001), but not with serum β2-microglobulin (β2-MG), C-PTH and aluminum levels. The SCDs of painful shoulders and the HCDs of painful hips were wider than those of asymptomatic shoulder and hip joints. In long-term HD patients, mean-SCD and mean-HCD were significantly wider in patients who had had CTS surgery or who had cystic radiolucency (CRL) of wrist joints, compared with those who had not have CTS surgery or CRL. Echo-free spaces were detected around the biceps tendon or subdeltoid bursa in 13 out of 103 patients, and these 13 shoulders had wide SCDs of more than 7mm. Histological examination of the shoulder joints revealed synovitis, synovial proliferation with marked cellular infiltration, and β2-MG amyloid deposits. MRI of the hip joints showed fluid retention and synovial thickening. This study showed that joint capsule swelling of the shoulder and hip increased gradually as HD duration increased. SCD and HCD, in which joint effusion and synovial thickening are involved, were wider in patients with dialysis arthropathy and a part of HD-related amyloidosis than in patients without it.